HER2, EGFR and TOPIIA gene amplification and protein expression in synovial sarcoma before and after combined treatment - Ptaszyński, Konrad; Szumera-Ciećkiewicz, Anna; Zakrzewska, Klara; Tuziak, Tomasz; Mrozkowiak, Anna; Rutkowski, Piotr (Polish Journal of Pathology, 2009)
Synovial sarcoma (SyS) occurs mostly in young adults and is characterized by an aggressive course. Combined treatment including chemotherapy, radiotherapy and surgical excision of the tumour is still not satisfactory, with mean 5-year survival of 30-50%. New targeted treatment options have appeared recently, e.g. HER2 and EGFR antagonists. Initial studies have revealed immunohistochemical overexpression of the EGFR in SyS; therefore trials with EGFR antagonist therapy have commenced. The aim of our study was to evaluate the status of HER2, EGFR and TOPIIA in SyS before and after combined therapy. Immunohistochemistry and FISH tests were performed. Significant discrepancies between protein expression and gene status were found. The authors discuss the potential reasons for that phenomenon.